Evaluating the Benefits of Moringa and Neem Leaf Extracts in Broilers - Asim Shahzad Khan; Muhammad Asif Raza; Shahid Ali Rajput; Naheed Bano; Atif Rehman; Riffat Yasin; Muhammad Asghar; Muhammad Uzair Khan (BioScientific Review, 2025)
Background. Plant extracts are among the alternatives to antibiotics. These are regarded as typically safe for animals. Neem and moringa are indigenous and well-known medicinal plants of Pakistan. However, limited studies have been conducted on these plants for their impacts on broilers. In this regard, this study was conducted at the experimental sheds of C-Block in Muhammad Nawaz Shareef (MNS) University of Agriculture, Multan, Pakistan.Method. A total of 144-day-old chicks were bought and kept in a single group for 7 days. They were weighed and 108 birds with average weights were placed into 12 replicates (9 chicks/replicate) which were allotted names including Gr-1, Gr-2, Gr-3, and Gr-4. Gr-1 was offered only a basal diet, whereas Gr-2, Gr-3, and Gr-4 were supplemented by moringa (4%), neem (4%), and moringa (4%) + neem (4%) leaf extracts respectively in water at 50ml/l. Two rations were prepared.  The starter was given for the first 3 weeks and the finisher till the end. Birds were vaccinated. Growth performance data was collected weekly. On the completion of the trial, blood samples were taken (5ml/bird) from 2 birds / replicates for the analysis of blood biochemical parameters. Moreover, 2 birds/replicate were euthanized and carcass samples were collected. The results were statistically analyzed.Results. The results of the experimental trial depicted that an addition of 4% Azadiracta indica (neem) leaf extract at 50ml/l showed better results.Conclusion. Neem leaf extract is suggested to be used in broilers as a cheap and effective growth promoter without any side effects.